MANFAAT BERMAIN TERHADAP PERKEMBANGAN KOGNITIF ANAK - Isti'adah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Ngawi, 2024)
ABSTRACT Playing is something that is done fun without any coercion. In the children age, they tends to spend some time to play. In the adult’s view, playing may be interpreted as only limited to having fun without a clear purpose. But for children, playing has their own essence. Play has many benefits including developing creativity and increasing cognitive. Cognitive children is all things that related to the intelligence of the mind and way of thinking of a person. When they are playing, the entire senses of the child will be testimony and experience good developent in physical and cognitive physical matters.